First record of Larsonella pumilus (Teleostei: Gobiidae) from Japan, with phylogenetic placement of the genus Larsonella - Hanahara, Nozomi; Higashiji, Takuo; Shinzato, Chuya; Koyanagi, Ryo; Maeda, Ken (Zootaxa, 2019)
During a survey of deep-sea fauna, using a Remotely Operated Vehicle, a single specimen (21.6 mm in standard length) of Larsonella pumilus (Larson & Hoese, 1980) was collected at a depth of 214 m off the coast of Okinawa Island, Japan. It represents the first record of this species from Japan. The collection site was far deeper than previous reports for this species. This suggests that the main habitat of L. pumilus is deeper than previously recognized and it may explain the paucity of records of this species. As the previously available morphological description of L. pumilus was based on only a single specimen (holotype), this new specimen is described herein. Its morphology corresponds closely to the original description of the holotype, except that faint melanophores are arranged radially around the eyes and scattered on the trunk and the fins. Mitochondrial genome sequences of L. pumilus and 19 related species demonstrate close relationships between L. pumilus and the genus Priolepis. These data also indicate that the genus Priolepis is not monophyletic.